IS INSTAGRAM USEFUL FOR STUDENTS? THE STUDENTS’ ENTHUSIASM IN UTILIZING INSTAGRAM IN WRITING - Isnaeni Wahab; Syahira Syahira; Heriyanti Tahang (Universitas islam Negeri Alauddin Makassar, 2023)
Writing is seen as a difficult skill that persists among the students which affected the students' writing test scores and lack enthusiasm in writing. From this primary issue, an effective tool is needed in learning both inside and outside the classroom, one of which is the use of Instagram which is collaborated in learning to write. So, this study aimed to investigate students' enthusiasm in using Instagram as a learning tool for text-writing. This study used quantitative research as its method and the instrument used in this research was questionnaires. The population of this study was students at SMA KARTIKA XX-I Makassar and the number of samples were 28 students to gain the data needed. The analysis of the data shows that students got 32% in the interested classification and 68% in strongly interested. So, it can be said students might more enthusiasm for writing by using Instagram as a social media platform.